Fetal placental inflammation is associated with poor neonatal growth of preterm infants: a case-control study. (October 2013) - Trevisanuto, Daniele; Peruzzetto, Carla; Cavallin, Francesco; Vedovato, Stefania; Cosmi, Erich; Visentin, Silvia; Chiarelli, Silvia; Zanardo, Vincenzo
Abstract Objective: To determine whether there is an association between histological chorioamnionitis (HCA) and postnatal growth of preterm infants in the neonatal period. Method: This case–control study is part of a larger prospective histological study on placentas performed in all deliveries prior to 32 weeks of gestation. Eligible cases involved all placentas with a diagnosis of HCA. Control subjects were those without HCA, matched 1:1 with case subjects according to gestational age (±1 week). Placental inflammatory status and serial weight gain were analyzed for all infants during the first four postnatal weeks. Based on placental inflammation extension, HCA was defined as maternal HCA (MHCA) or fetal HCA (FHCA). Results: Of the 320 mother–infant pairs, 71 (22.1%) presented with HCA (27 MHCA and 44 FHCA). Decreases in weight gain at 21 and 28 days were associated with the presence of FHCA (β coefficient ± SE = −4.40 ± 2.21, p = 0.05 and −6.92 ± 2.96, p = 0.02, respectively), whereas no significant differences were found between MHCA and no-HCA groups. FHCA and MHCA were not identified as risk factors of weekly weight gain, after adjusting for possible confounders (maternal ethnicity, parity, smoking during pregnancy, infant gender, IUGR status, SGA status, antenatal steroids, total fluid intake, late-onset sepsis, BPD). Conclusions: We found an association between fetal placental inflammation and poor neonatal growth but we were not able to identify a specific week wherein weight gain could be mostly affected. Placental findings may be used to identify preterm infants at risk of postnatal growth failure.